Telecommunication principles. - RENTON, R.N (Pitman, 1965)
TABLA DE CONTENIDO: 1 Electrons. 2 The D.C circuit. 3 Power and energy. 4 Celis. 5 Electrostatics. 6 Magnetism. 7 Electromagnetism. 8 Generators. 9 The D.C motor. 10 Alternating currents. 11 A.C. transmision. 12 Maters and measurements. 13 Valve electronics. 14 Transistor electronics. 15 Sound